A Pilot Project to Evaluate the Acceptability of Serum Clozapine Level Monitoring by Finger-prick Method in an Adult Community Mental Health Team (CMHT) - Sadia Tabassum Javaid; Ravindra Belgamwar; George Horton (BJPsych Open, 2025)
Aims: Clozapine is a cornerstone in treating resistant schizophrenia, with evidence linking threshold plasma levels to positive clinical outcomes. The Maudsley Guidelines recommend levels of 250–420 µg/L for an adequate trial. Our trust requires trained staff to collect venous samples, with results taking several days. The updated clozapine pathway suggests checking levels at initiation and 12 months, prompting consideration of the Saladax MyCare Insite Analyzer. This point-of-care device uses a finger-prick sample and delivers results in 7 minutes. Despite promising studies, its effectiveness depends on local acceptance, warranting a pilot.